Chapter Educare e istruire con i fumetti: alcune ipotesi sulla Storia contemporanea - Bianchi, Roberto (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper highlitghts the role played by comics in stimulating formative and cultural literacy processes held in contemporary world. After having devoted time to the Italian situation, it highlights the potential and the limits comics met on an educational basis, as it is necessary to use them critically and on a reasonable basis. After the First World War, comics were spread extensively for war propaganda aims. Afterwards, the Great War has consolidated its presence in essays and volumes, as several comics about it were published, almost of all for its anniversary.